Ceria-Co-Cu-based SOFC anode for direct utilisation of methane or ethanol as fuels. (14th February 2020) - Sarruf, Bernardo Jordão Moreira; Hong, Jong-Eun; Steinberger-Wilckens, Robert; de Miranda, Paulo Emílio Valadão
Abstract: Nickel-free solid oxide fuel cell anodes are an object of study for applications that aim at utilising primary carbonaceous fuels to generate power. In this study, a ceria-Co-Cu anode is produced and tested with hydrogen, methane and ethanol fuels at various temperatures. The produced catalysts were characterised by X-ray analysis and H2 temperature-programmed reduction (TPR). Catalytic tests were performed and compared with the material under electrochemical operation. The cells were electrochemically characterised by recording i-V plots. The samples were assessed post-test for eventual carbon deposits by Raman spectroscopy investigations and temperature-programmed oxidation (TPO) analysis. The cells were able to operate with hydrogen, methane as well as ethanol, directly fed to the anode, with maximum power densities ranging from 400 to 540 mW.cm −2, depending on the fuel stream utilised. The cells also kept their integrity demonstrating coking resistance for over 24 h of continuous operation. Important discussions and conclusions are drawn about carbon formation and the role of each compound in the anode composition. The bimetallic cell (ceria-Co-Cu) is herein compared to monometallic ones (ceria-Co and ceria-Cu) that served as baselines. The advantages of the bimetallic composition are listed and evaluated throughout the discussions. Highlights: Nickel-free SOFC anode operating with high performance with methane and ethanol. Continuous operation with carbon-rich fuels without coking. Operation with direct primary fuels with no reforming agents.